2006
DOI: 10.1111/j.1524-6175.2006.06042.x
|View full text |Cite
|
Sign up to set email alerts
|

Organ Systems Dependent on Nitric Oxide and the Potential for Nitric Oxide‐Targeted Therapies in Related Diseases

Abstract: Nitric oxide (NO) is a universal messenger mol-1 This simple molecule appears to occur in virtually every tissue, and impairment of NO bioactivity has been documented in a wide array of diseases.1,2 There are 3 known isoforms of NO synthase (NOS), the enzyme necessary for the production of NO from its substrate, L-arginine.1,2 These isoforms include endothelial NOS (eNOS), found primarily in the endothelium of blood vessels and airway epithelium; neuronal NOS (nNOS), concentrated in nerve endings and in tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 161 publications
(260 reference statements)
0
7
0
Order By: Relevance
“…It has even been postulated that AD is primarily a vascular disorder with neurodegenerative consequences, with the initial pathogenic insult arising from cerebral hypoperfusion, and with impairment of NO bioactivity contributing to the progression of the disease (Hollenberg 2006). Indeed, reduced cerebral blood flow (Iadecola et al 1999) and a reduction in vasoreactivity (Vicenzini et al 2007) have been found in AD patients.…”
Section: Neurovascular Interactions In Admentioning
confidence: 97%
See 1 more Smart Citation
“…It has even been postulated that AD is primarily a vascular disorder with neurodegenerative consequences, with the initial pathogenic insult arising from cerebral hypoperfusion, and with impairment of NO bioactivity contributing to the progression of the disease (Hollenberg 2006). Indeed, reduced cerebral blood flow (Iadecola et al 1999) and a reduction in vasoreactivity (Vicenzini et al 2007) have been found in AD patients.…”
Section: Neurovascular Interactions In Admentioning
confidence: 97%
“…Inducible NOS (iNOS) is produced by astroglial cells and neurons in response to inflammatory conditions. Endothelial NOS (eNOS) influences vasodilation, and thus the state of cerebral perfusion (Hollenberg 2006).…”
Section: Nitric Oxidementioning
confidence: 99%
“…Nitric oxide is a messenger molecule that performs diverse biologic functions, appears to occur in virtually every tissue, and impairment of nitric oxide bioactivity has been documented in a wide variety of diseases (22). Nitric oxide has been suggested to play a role in diseases of blood vessels, the heart, brain, lungs, liver, kidney, stomach, the immune system, musculoskeletal, and reproductive systems.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Indeed, drugs that provide or "donate" NO have been used for many years to treat or prevent angina pectoris pain or to manage hypertensive crises.…”
Section: No-therapeutic Interventionsmentioning
confidence: 99%